2020
DOI: 10.1111/bjd.19554
|View full text |Cite
|
Sign up to set email alerts
|

An economic evaluation of the randomized controlled trial of topical corticosteroid and home‐based narrowband ultraviolet B for active and limited vitiligo (the HI‐Light Vitiligo Trial)*

Abstract: Background Economic evidence for vitiligo treatments is absent. Objectives To determine the cost-effectiveness of (i) handheld narrowband ultraviolet B (NB-UVB) and (ii) a combination of topical corticosteroid (TCS) and NB-UVB compared with TCS alone for localized vitiligo. Methods Cost-effectiveness analysis alongside a pragmatic, three-arm, placebo-controlled randomized controlled trial with 9 months' treatment. In total 517 adults and children (aged ≥ 5 years) with active vitiligo affecting < 10% of skin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The trial protocol has been published previously 29,30 . No changes were made to the eligibility criteria or outcome measures after trial commencement.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The trial protocol has been published previously 29,30 . No changes were made to the eligibility criteria or outcome measures after trial commencement.…”
Section: Methodsmentioning
confidence: 99%
“…The study was a multicentre, three‐arm, parallel‐group, pragmatic, placebo‐controlled randomized controlled trial, with nested health economics and process evaluation studies (reported separately) 30 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations